2020
DOI: 10.1590/s1984-29612020084
|View full text |Cite
|
Sign up to set email alerts
|

Parasitological assessment in hybrids Serrasalmidae fish farmed in Brazil

Abstract: This study evaluated the parasitic fauna of hybrids tambacu (Colossoma macropomum × Piaractus mesopotamicus) and patinga (P. mesopotamicus × Piaractus brachypomus) and their host-parasite-environment interaction during the warm and cold seasons in two fish farms located in the State of Mato Grosso do Sul, Brazil, South America. A total of 120 fish, being 60 fish for species (30 in the warm season and 30 in the cold season) were examined. Water quality was measured weekly to evaluate the interaction between env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Animals' gill arches were removed and fixed in 5% formalin. Parasites were quantified in a Petri dish (150 × 20 mm) with the help of a stereomicroscope (Feldman Wild Leitz ® ) as suggested by Jerônimo et al (2020). The ecological terms of prevalence, mean parasite intensity and mean parasite abundance were determined in line with Bush et al (1997).…”
Section: Parasitological Analysis and Treatment Effectivenessmentioning
confidence: 99%
“…Animals' gill arches were removed and fixed in 5% formalin. Parasites were quantified in a Petri dish (150 × 20 mm) with the help of a stereomicroscope (Feldman Wild Leitz ® ) as suggested by Jerônimo et al (2020). The ecological terms of prevalence, mean parasite intensity and mean parasite abundance were determined in line with Bush et al (1997).…”
Section: Parasitological Analysis and Treatment Effectivenessmentioning
confidence: 99%
“…The authors also indicated that hybrids of serrasalmids are more vulnerable to parasites, harbouring a high parasitic diversity in relation to parental species. 84 Banerjee and Bandyopadhway 71 also reported the influence of the seasons on the parasite fauna of the teleosts Labeo rohita, Catla catla, Cirrhinus mrigala, Labeo bata, Cyprinus carpio and Channa punctatus in fish farms of Nadia and Hooghly, India. In the study, trichodinids, such as Trichodina spp.…”
Section: Seasonalitymentioning
confidence: 97%
“…Another Copepoda parasite that also has this behaviour is the cosmopolitan crustacean L. cyprinacea, whose life cycle is facilitated in warmer months, causing, not rarely, severe outbreaks of mortality in farmed fish and natural environments. 66 Jerônimo et al 84 when evaluating the dynamics of L. cyprinacea in tambacu hybrids (C. macropomum × P. mesopotamicus) and patinga (P. mesopotamicus × P.…”
Section: Seasonalitymentioning
confidence: 99%
See 2 more Smart Citations